Adipokines, and not vitamin D, associate with antibody immune responses following dual BNT162b2 vaccination within individuals younger than 60 years - Pavel-Tanasa, Mariana; Constantinescu, Daniela; Cianga, Corina Maria; Anisie, Ecaterina; Mereuta, Ana Irina; Tuchilus, Cristina Gabriela; Cianga, Petru (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) led to a global health outbreak known as the COVID-19 pandemic which has been lasting since March 2020. Vaccine became accessible to people only at the beginning of 2021 which greatly helped reducing the mortality rate and severity of COVID-19 infection afterwards. The efficacy of vaccines was not fully known and studies documenting the immune responses following vaccination are continuing to emerge. Recent evidence indicate that natural infection prior vaccination may improve the antibody and cellular immune responses, while little is known about the factors influencing those processes. Here we investigated the antibody responses following BNT162b2 vaccination in relation to previous-infection status and age, and searched for possible biomarkers associated with the observed changes in immune responses. We found that the previous-infection status caused at least 8-times increase in the antibody titres, effect that was weaker in people over 60 years old and unaltered by the vitamin D serum levels. Furthermore, we identified adiponectin to positively associate with antibody responses and negatively correlate with pro-inflammatory molecules (MCP-1, factor D, CRP, PAI-1), especially in previously-infected individuals.